PENGARUH COST OF DEBT, BEBAN PAJAK PENGHASILAN DAN KEBIJAKAN DIVIDEN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN CONSUMER NON CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2021 - Suci Ayu Rahmawati; Wiwit Irawati (Jurnal Ilmiah Akuntansi & Bisnis, 2022)
This study aims to examine and analyze the effect of the cost of debt, income tax burden and dividend policy on earnings management in consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2017-2021. This research uses quantitative and associative research types from secondary data sources. The population used in this study were 104 consumer non-cyclicals companies listed on the IDX. The research sample was selected using a purposive sampling technique and a sample of 20 companies was obtained. Data collection techniques are documentation studies and non-participant observations. The data analysis technique used is panel data regression analysis with the Eviews 9 test tool. The results show that the cost of debt, income tax expense and dividend policy simultaneously influence earnings management in consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2017- 2021.